Graphics design work: Singalang Burong / Fernandez Randy Patrick - Patrick, Fernandez Randy (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The Singalang Burong is popular in Sarawak especially among the Iban ethnic. The artwork highlights the distinctiveness of the Singalang Burong statue's motif about the Iban ritual through the understanding of the media dimension. The design of the artworks adapts the motives of the Singalang Burong which are portrayed in the painting, drawing and sculpture.